Biosecurity and risk analysis for cow-calf enterprises: a simulation model for Bovine Viral Diarrhea Virus - Smith, Rebecca Lee (Kansas State University, 2007)
A Monte Carlo model was developed to determine the cost-effectiveness of different biosecurity strategies for Bovine Viral Diarrhea Virus (BVDV) on cow-calf farms. Where possible, risk distributions were defined in the course of a critical literature review covering all publications since 1990 relevant to BVDV on cow-calf farms. The prevalence of persistent infections (PIs) in adult cows was unknown, so a survey of viremia in 2,990 adult cows for sale in the Midwest during 2006 was performed; prevalence was calculated to be 0.07%. In order to validate a newly developed RT-nPCR for pooled serum used for the survey, sensitivity was determined based on 100 known viremic serum samples; sensitivity was 95%, with no detectable effect of strain type. A Monte Carlo model was developed to calculate the risk of introducing BVDV to a cow-calf herd and number of PIs introduced in one year, based on herd imports and biosecurity strategies. The results of that model were integrated with a stochastic SIR model for the spread and impact of BVDV through a cow-calf herd over 10 years, based on herd size and control strategies. The resulting model was integrated with a stochastic model for the cost of both the biosecurity and control measures used and the financial impact of BVDV infection on the herd over 10 years. The lowest risk option of 14 biosecurity strategies were calculated for 400-, 100-, and 50-head herds with 8 different import profiles, and management factors that increase financial risk due to BVDV were determined.
Keywords: biosecurity; risk analysis; BVDV; beef; cow-calf; epidemiology; Biology, Veterinary Science (0778)